The Strategic, Curious & Skeptical Learner : Australian Public Librarians and Professional Learning Experiences. Issue 3 (4th May 2022) - Stephens, Michael; Partridge, Helen; Davis, Kate; Snyder, Margaret
ABSTRACT: This study used narrative inquiry to investigate the experiences of Australian public librarians with professional learning and development. Twelve librarians currently working in public libraries in Australia were interviewed. The interviews revealed stories that depicted the real experiences of professional learning for the librarians. These stories are represented in this paper via two components: five critical insights; and three personas. The five critical insights include: (i) there is not enough professional learning experiences (PLE) or learning culture in their library; (ii) PLE must be sought out personally and a major portion of PLE has to happen on their own time; (iii) PLE is primarily found online, and that utilizing social media is a crucial way to find PLE opportunities; and (iv) PLE opportunities are wanted. The three personas were articulated to best typify the different experiences of the Australian public librarians: the Strategic Learner, the Curious Ad Hoc Learner, and the Skeptical Learner. The study's findings have implications for how public libraries in Australia can support and enable a culture of professional learning and development.